Close oxygen coupled low-pressure chemical vapor deposition growth of high quality β - Ga2O3 on sapphire - Akyol, Fatih; Demir, Ilkay (ELSEVIER SCI LTD, 2022)
We report on the close oxygen coupled low-pressure chemical vapor deposition (COC-LPCVD) hetero-epitaxial growth of atomically smooth (-201) oriented beta-Ga2O3 on c-plane sapphire. Utilizing a dedicated line within the main tube, O-2 could be delivered to the substrate surface which enables effective control of growth regime. Under optimized conditions (Ga-rich and near stoichiometric feed rate), step flow growth was obtained with X-ray rocking curve full-width at half maximum of 0.09 degrees and 0.20 degrees at a growth rate of 0.49 mu m/h and 3.42 mu m/h, respectively. On the other hand, oxygen-rich growth at high growth rates produced in-plane rotational domains. In addition, the alignment of single crystal (-201) beta-Ga2O3 with respect to the sapphire offcut direction was revealed such that [-20-1] beta-Ga2O3 is along [11-20] (offcut direction) sapphire. This study demonstrates the potential of the versatile COC-LPCVD system on the thin film growth of high quality beta-Ga2O3.
Keywords: BETA-GA2O3; Engineering; Materials Science; Physics